ENTREPRENEURSHIP AND INNOVATION IN HEALTH: OPPORTUNITIES ANALYSIS - Aveni, Alessandro (Revista Coleta Científica, 2020)
The paper discuss health economics considering actual opportunities and the discussion about the current systems due to the Covid-19 pandemic. The analysis is exploratory based on a bibliographic search and a didactic approach to provide as a result the list of opportunities in the market. The work shows the importance of the health sector for national GDPs, the elements that characterize the health economy and the cognitive models used to define demand and supply of health goods. The result shows opportunities in different innovative areas such as health care services; diagnosis and therapeutics; financing and payment; well-being, platforms and support. The analysis focuses on health demand, a focus that differs from the classic economic approach that is based on the model of analysis of supply, a model still used mainly by the government in its management of the public health system.